Identification of the type of exercise therapy that affects functioning in patients with early‐stage amyotrophic lateral sclerosis: A multicenter, collaborative study. Issue 5 (30th July 2014) - Kamide, Naoto; Asakawa, Takashi; Shibasaki, Nobuhiko; Kasahara, Yoshio; Tamada, Yoshiki; Kitano, Kosuke; Kikuchi, Yutaka; Yorimoto, Keisuke; Kobayashi, Yoko; Komori, Testuo
Abstract Background The types of exercise therapy that have an effect on functioning in early‐stage amyotrophic lateral sclerosis patients are not well‐known. Aim To investigate the types of exercise therapy that have an effect on functioning in early‐stage amyotrophic lateral sclerosis patients. Methods The participants were consecutive amyotrophic lateral sclerosis patients who were prescribed exercise therapy at six institutions in Japan. All data (age, sex, site of onset and disease duration) were collected retrospectively from the patients' medical records. The amyotrophic lateral sclerosis functional rating scale‐revised scores were collected to assess patients' functioning at two time‐points, at baseline and during exercise therapy. Furthermore, details of the types of exercise therapy were investigated. The change in the amyotrophic lateral sclerosis functional rating scale‐revised score was calculated using the score at two time‐points. A multiple regression analysis was used to determine the effect of type of exercise therapy on the change in amyotrophic lateral sclerosis functional rating scale‐revised scores. Results The analysis included 156 participants. The interaction term of performance factor (walking training, standing training, and activities of daily living task training) was significantly associated with the change in the amyotrophic lateral sclerosis functional rating scale‐revised score, but the interaction term of the muscle function factor (resistance training and cycle ergometer training) was not. Conclusion The combination of performance task training appears to alleviate functional decline in early‐stage amyotrophic lateral sclerosis patients.